Efek ekstrak teh hijau (Camellia sinensis (L.) O. Kuntze var. assamica) terhadap berat badan dan kadar malondialdehid wanita overweight - Alpha Olivia Hidayati; Wiryatun Lestariana; Emy Huriyati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2012)
Background: Overweight and obesity were risk factors of various degenerative diseases. Green tea extract contains polyphenol compounds, particularly catechins which act as antioxidants, fat dissolvent and aid lipolysis. Thus, it is necessary to study the use of green tea as an alternative treatment to overcome overweight.Objective: To identify the effect of green tea extract supplementation on body weight and malondialdehide (MDA) level of overweight women in Yogyakarta District Health Office.Method: This was an experimental study with double-blind randomized controlled trial design. Subject of the study were divided into two groups; one group consumed green tea extract capsules and the other consumed placebo. Weight, 6 times 24 hours recall, and level of MDA were measured on every subject.Results: The results revealed that green tea extract has a weight-reducing effect and decrease MDA level of overweight women, though the reduction of weight and MDA level was not significant (p>0,05). Weight loss of 1.3% was observed in the treatment group, whereas the control group has an increase of 0.6% body weight, but the weight change was not significant (p=0.501, p=0.620). Changes in body weight after 12 weeks of treatment showed a significant disparity between the two groups (p=0.000). MDA level decreased by 10% in the treatment group compared to 8.3% in the control group. MDA levels pre and post intervention was significantly different in the treatment group (p=0.006), whereas in the control group there was no significant discrepancy observed (p=0.123). However, changes in MDA levels after 12 weeks of treatment showed no significant differences among groups (p=0.278). The mean nutrient intakes of subjects were still below the recommended dietary allowance (RDA), except for protein.Conclusion: Green tea extract had a weight-reducing effect and decrease MDA level of overweight women in Yogyakarta District Health Office, though the reduction was not statistically significant.